Corneal angiogenic privilege and its failure. (March 2021) - Di Zazzo, Antonio; Gaudenzi, Daniele; Yin, Jia; Coassin, Marco; Fernandes, Merle; Dana, Reza; Bonini, Stefano
Abstract: The cornea actively maintains its own avascular status to preserve its ultimate optical function. This corneal avascular state is also defined as "corneal angiogenic privilege", which results from a critical and sensitive balance between anti-angiogenic and pro-angiogenic mechanisms. In our review, we aim to explore the complex equilibrium among multiple mediators which prevents neovascularization in the resting cornea, as well as to unveil the evolutive process which leads to corneal angiogenesis in response to different injuries. Highlights: Cornea actively maintains its own avascular status. Corneal angiogenic privilege is a balance of neuro- immune- and endocrine mediators. The pattern of corneal neovascularization changes with the specific disease or injury. Loss of angiogenic privilege is critical risk factor in corneal allograft rejection. Proangiogenic mediators are prospective target of future treatments.